Development of bread wheat stocks with high degree of resistance to Karnal bunt by combining genes from diverse sources - Sharma, Indu; Sharma, R.C.; Bains, N.S.; Sharma, A.K.; Sohu, V.S. (Indian Phytopathology, 2011)
The strategy of crossing diverse Karnal bunt (KB) resistant wheat stocks with each other was followed to develop high degree of KB resistance with the ultimate objective of developing KB-free stocks. Homozygous lines were derived from twenty three ‘resistant’ x ‘resistant’ crosses involving seven diverse KB resistant stocks (‘ALDAN ‘S’/IAS 58’, ‘CPAN 3045’, ‘H 567.71/3*PAR’, ‘CMH 77.308’, ‘HD 29’, ‘HP 1531’ and ‘W 485’) for this purpose. The homozygous ‘resistant x resistant’ cross derivatives was initially subjected to repeated KB screening (4-8 years) at one location under artificial inoculation. Thirty one lines which maintained KB-free status were promoted to multilocation evaluation (Delhi, Pantnagar, Karnal, Hisar and Dhaulakuan), covering a wide spectrum of environmental and pathogen diversity in India. Stocks which retained KB-free status (11 lines) or showed a distinctly higher degree of resistance (under artificial inoculations) than parental stocks (another 10 lines with less than 1% infection) resulting from pyramiding of genes effective against a wide spectrum of pathogen populations at multilocations were selected. The genetic implications and role of these stocks in resistance breeding are discussed.